Functional Logic Programming. - ANTOY, SERGIO; HANUS, MICHAEL (Communications of the ACM, 2010)
The article discusses the features of functional logic programming, which supports specification, prototyping, and application programming within one declarative language. According to the article, functional languages are based on mathematical functions while logic languages are based on predicate logic. Functional logic languages combine the features of both paradigms. The Curry functional logic language that produces a standard for research, teaching, and application of functional logic programming is noted. The functional logic programming techniques for application programming are discussed.